2020
DOI: 10.1111/jfbc.13556
|View full text |Cite
|
Sign up to set email alerts
|

Protection against acute renal injury by naturally occurring medicines which act through Nrf2 signaling pathway

Abstract: The cellular defense pathway plays a key role in maintaining the homeostasis, tissues and organisms. Nuclear factor E2-related factor 2 (Nrf2), as a key cell signaling pathway, plays an important role in encoding detoxification enzymes and other stress response mediators. Recent studies have shown that it is closely related to the prevention and treatment of acute kidney injury (AKI). Therefore, this article reviews the protective effects of Nrf2-related signaling pathways on acute kidney injury, and summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Pathway in Protecting against Intestinal I/R Injuries. The protective role of Nrf2 activation with involvement of its downstream pathways such as HO-1 and NQO1 is characterized by inhibiting inflammation, oxidative stress, and apoptosis [29][30][31], which are involved in ameliorating kidney [32], brain [33], and myocardial injuries [34]. 3.5.2.…”
Section: Sesamin-induced Activation Of the Nrf2 Signalingmentioning
confidence: 99%
“…Pathway in Protecting against Intestinal I/R Injuries. The protective role of Nrf2 activation with involvement of its downstream pathways such as HO-1 and NQO1 is characterized by inhibiting inflammation, oxidative stress, and apoptosis [29][30][31], which are involved in ameliorating kidney [32], brain [33], and myocardial injuries [34]. 3.5.2.…”
Section: Sesamin-induced Activation Of the Nrf2 Signalingmentioning
confidence: 99%
“…A lot of natural compounds including alkaloids, phenolics, and terpenes in chrysanthemum have been identified as antioxidants [ 6 ]. For them, the predominant effects may involve the activation of Nrf2-related antioxidant pathways and scavenging of free radicals [ 7 , 8 , 9 ]. However, researchers found that the biological activities of natural extracts are much higher than those of single bioactive molecules due to the interaction between molecules at pharmacodynamic and pharmacokinetic levels, suggesting that the synergistic effect between multiple compounds cannot be overlooked [ 10 ].…”
Section: Introductionmentioning
confidence: 99%